Minyak Sawit Merah: Karakteristik Nutrisi, Bioaktif, Potensi Kesehatan, dan Aplikasi dalam Pangan Fungsional Sumber Antioksidan - Goneril, Davin; Septi Niranti Hidayat, Dwi; Septiani, Emilia (Politeknik Negeri Ketapang, 2025)
Red palm oil is reddish crude palm oil (CPO) refined olien fraction without being bleached. This commodity has the potential to be developed from the industrial to health sectors. Red palm oil can be potential antioxidant source functional food, however comprehensive reviewing chemical and bioactive profile, health evidence, and antioxidant activity in functional food never been conducted. The review is using descriptive method as narrative review, summarizing the nutritional content, bioactives, health potential, and functional foods utilization from 2015-2025. Red palm oil is dominated by saturated (37.83%-65.62%) and monounsaturated (27.30%-43.54%) fatty acids. The bioactive compounds found were carotenoids, tocopherols, phytosterols, squalene, flavonoids, and phenolics, that can act as antioxidants, anti-inflammatories, blood vitamin A enhancers, antidiabetics, and antiproliferatives. In functional food processing, such as chocolate spread, mellorine, bagelan, and ground coffee providing DPPH radicals inhibition around (7.091%-82.10%). The study shows that red palm oil is considered balanced between the contained fatty acids, while high in antioxidants (Tocotrienol, β-carotene, sitosterol, and squalene) which depended on the cultivation, post-harvest handling, and processing. The potential health function provided as a source of functional food antioxidants affected by the processing and ingredients combination, which shows the potential for diversification in the further research.